2020
DOI: 10.1515/npprj-2020-0043
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine dioxide bleaching of nineteen non-wood plant pulps

Abstract: Bleaching of unbleached and oxygen delignified pulps from nineteen non-wood plants has been evaluated in elemental chlorine free bleaching. Chlorine dioxide charge (kappa factor 0.15, 0.20 and 0.25) and temperature (70 and 85 °C) in the delignification stage (D) were varied. Chlorine dioxide (ClO2) charge and temperature exhibited lower kappa number and higher brightness after alkaline extraction (EP) stage. High temperature ClO2 delignification (DHT) exhibited higher final pulp brightness. The final brightnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A bleaching process can remove lignin and other impurities. By removing those barriers, the cellulose becomes more accessible for carboxymethylation, leading to a higher yield of CMC during the subsequent processing steps [ 42 ]. The bleaching process can alter the properties of cellulose fibers by enhancing the reactive towards the carboxymethylation reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A bleaching process can remove lignin and other impurities. By removing those barriers, the cellulose becomes more accessible for carboxymethylation, leading to a higher yield of CMC during the subsequent processing steps [ 42 ]. The bleaching process can alter the properties of cellulose fibers by enhancing the reactive towards the carboxymethylation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The highest decrease in kappa number occurred after chemical bleaching three times (3 BT). Ferdous, Quaiyyum, and Jahan [ 42 ] also reported that the kappa number of rice straw pulp was lower after delignification with chlorine dioxide. This could be related to the acid bleaching of the lignin as described by Ferdous et al [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the last years, several promising approaches in all fields of established papermaking procedures have been investigated at a laboratory or pilot scale, to overcome the limitations and challenges of non-wood pulping. These methods have constituted nonwood plant fibers as a reasonable candidate to replace wood fibers, especially replacing hardwood as the pulp feedstock (El-Sayed et al 2020;Ferdous et al 2020;Sharma et al 2020a;Jahan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The bleaching process is a necessary step to brighten pulp by treating it with chemicals composed of chlorine or oxygen, e.g., hypochlorite, chlorine, sodium hydroxide, chlorine dioxide, and hydrogen peroxide. The remaining lignin and other coloring matters such as tannin and gums are removed during this process [7]. Generally, the pulp is bleached in several stages and the bleaching sequence depends on chemical used, time, and temperature.…”
Section: Introductionmentioning
confidence: 99%